2021
DOI: 10.1371/journal.pone.0249351
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of leaf water content from hyperspectral data of different plant species by using three new spectral absorption indices

Abstract: The leaf equivalent water thickness (EWT, g cm−2) and fuel moisture content (FMC, %) are key variables in ecological and environmental monitoring. Although a variety of hyperspectral vegetation indices have been developed to estimate the leaf EWT and FMC, most of these indices are defined considered two or three specific bands for a specific plant species, which limits their applicability. In this study, we proposed three new spectral absorption indices (SAI970, SAI1200, and SAI1660) for various plant types by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 51 publications
1
3
0
1
Order By: Relevance
“…The performance metrics of the RF models showed that a good accuracy (6.9% of RMSE and 14.0% of NRMSE) was achieved when all the genotypes and all moisture content intervals were considered in the models (Table 3). Similar results were reported by Li et al (2021) to estimate the moisture content of three species of trees, who achieved an NRMSE between 8.6% and 13.9%. The models evaluated to estimate the moisture content might be affected by errors in the estimation in some moisture content intervals due to limits in the range of data used to train the model (Shah et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…The performance metrics of the RF models showed that a good accuracy (6.9% of RMSE and 14.0% of NRMSE) was achieved when all the genotypes and all moisture content intervals were considered in the models (Table 3). Similar results were reported by Li et al (2021) to estimate the moisture content of three species of trees, who achieved an NRMSE between 8.6% and 13.9%. The models evaluated to estimate the moisture content might be affected by errors in the estimation in some moisture content intervals due to limits in the range of data used to train the model (Shah et al, 2019).…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, the raw spectra in Figure 2 a demonstrated that the absorption peaks of the samples are mainly located in the NIR region. The peak of absorbance within the NIR region for water and apple cider is located at 973 nm, which is associated with the second overtone of the symmetric and asymmetric OH-stretching bands [ 40 , 41 , 42 ]. The apple cider generally contains up to 94% of water content [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The rRMSE was used to compare the performance of regression models across different algorithms and maize water indicators. To compute rRMSE, the RMSEs from each model were normalised using the mean of each variable and then expressed as a percentage [51].…”
Section: Accuracy Assessment Of Derived Maize Water Content Modelsmentioning
confidence: 99%